A review of organochlorine and metal pollutants in marine mammals from Central and South America - Borrell, Assumpción; Aguilar, Alex (J. Cetacean Res. Manage., 1999)
Published data on pollutants found in marine mammals from Central and South America are limited. Few species have been studied (18) and sample sizes are usually too small to allow for proper assessment of trends or impacts of pollutants on the populations being studied. The only exceptions to this are the franciscana dolphin from Argentina and the spotted dolphin from the eastern tropical Pacific: the former population studied for organochlorines and the latter for heavy metals. Information on organochlorine levels, mainly on PCBs and DDTs, suggests low levels of exposure when compared to other regions of the world. The ratio DDT/PCB is higher than in other areas, which indicates the predominance of agricultural contamination over that of industrial origin. The generally low DDE/tDDT ratio, particularly in southern America, indicates a recent usage of this pesticide in the region. Levels of mercury were moderate overall, although marine mammals from the areas where contamination by this metal is likely to be higher, such as the Amazon river, have not been studied in this regard. In contrast, mean cadmium and zinc concentrations were higher overall than those in the range typical for northern marine mammals, while copper and lead levels were comparatively low, although information on these latter metals is extremely limited. The lack of comprehensive, long-term studies makes a sound evaluation of the impact of pollutants on the marine mammals from the region unfeasible